Concept development through the inclusion exclusion approach effects on mathematics understanding and achievement - Catubay,Jenny Jesusa J. (2008)
An alternative-teaching strategy anchored on constructivism - the inclusion-exclusion approach (I-EA) - was designed to determine the effects on Grade 5 students' conceptual understanding and mathematics achievement. A quasi-experimental design, particularly the pretest-posttest control group design, was employed. Results of the analysis showed that the students who were taught the inclusion-exclusion approach achieved higher mean score in the Achievement and Concept Tests suggesting the greater effectiveness of the I-EA in helping students gain knowledge as well as enhancing understanding of mathematical concepts. Varying the teaching strategy by the constructivist approach was recommended to elevate students' achievement and conceptual understanding.
Thesis (M.A. Elementary Mathematics)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines -- Laoag City (Ilocos Norte); Public schools -- Philippines -- Laoag City (Ilocos Norte); Mathematical ability